2018
DOI: 10.1002/dc.24068
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid nodule size calculated using ultrasound and gross pathology as predictors of cancer: A 23‐year retrospective study

Abstract: Background Thyroid nodules are very common. Ultrasound (US) and fine needle aspiration (FNA) are both integral in cancer screening. This study investigated the concordance between thyroid nodule sizes measured by US and gross pathologic examination and their relationship with malignancy. Methods A retrospective design was used to select consecutive patients with proven carcinoma of the thyroid. The number and maximum diameter of nodules, rates and types of malignancy, as well as predictors of malignancy were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
3
10
0
6
Order By: Relevance
“…The study reported that the risk of malignancy for thyroid nodule(s) was higher for those having 2 cm or lesser size in ultrasound. These results of the study were consistent with the results of retrospective studies 5,19 and prospective study 20 but were contraindicated with the results of retrospective studies. 8,9,[21][22][23] The papillary thyroid carcinoma has an inverse relationship with thyroid nodule size.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The study reported that the risk of malignancy for thyroid nodule(s) was higher for those having 2 cm or lesser size in ultrasound. These results of the study were consistent with the results of retrospective studies 5,19 and prospective study 20 but were contraindicated with the results of retrospective studies. 8,9,[21][22][23] The papillary thyroid carcinoma has an inverse relationship with thyroid nodule size.…”
Section: Discussionsupporting
confidence: 85%
“…These results of the study were consistent with the results of retrospective studies. 5,12,19 The size difference by ultrasound finding is required to be in consideration to avoid unnecessary surgery. The study reported that the risk of malignancy for thyroid nodule(s) was higher for those having 2 cm or lesser size in ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…A large nodule size ≥30 mm showed a higher malignancy risk than smaller nodules in intermediateand low-suspicion nodules [27]. Zhao et al concluded that thyroid nodule size is inversely related to malignancy risk, as larger nodules have lower malignancy rates [26]. Our findings support the results of other studies highlighting that there is still uncertainty in relation to the impact of the size of a solitary thyroid nodule and the risk of malignancy.…”
Section: Discussionsupporting
confidence: 88%
“…Zhao et al concluded that nodule size estimated by ultrasound (US) shows relatively good correlation with final pathologic size. However, thyroid nodules should undergo FNA regardless of size [26].…”
Section: Discussionmentioning
confidence: 99%
“…10 Malignite ve nodül boyutu korelasyonu ile ilgili yapılmış çok sayıda çalışma olmasına rağmen, nodülün patolojik ve sonografik boyutu arasında korelasyonu değerlendiren çalışma sayısı azdır. 6,8,11 Bu çalışmada tiroid nodülü olan hastaların yönetiminde önemli bir parametre olan USG'de raporlanan nodül boyutu ile patolojik nodül boyutu arasındaki uyumluluk durumunu tiroidektomi yapılan hastalarda değerlendirmeyi amaçladık. USG ve İİA; tiroid nodülü olan hastaların değerlendirmesinde kullanılan temel değerlendirme yöntemleridir.…”
Section: Introductionunclassified